The Characteristics of Corporate Environmental Responsibility in Climate Change Litigation - Zhan, Dan (International Journal of Social Sciences and Public Administration, 2025)
Climate change has affected human beings around the world, and the atmospheric system on which it depends is changing. Under the influence of climate change, extreme weather occurs frequently. In order to respond more actively to global climate change, climate change litigation is emerging globally, involving more subjects such as governments or enterprises in climate governance actions. This paper summarizes the characteristics of climate change litigation against enterprises from the existing climate change litigation cases, mainly including the legal basis of litigation and the change of claims in litigation.